Lifetime Smoking and Asthma: A Mendelian Randomization Study - Shen, Ming; Liu, Xin; Li, Guoqi; Li, Zhun; Zhou, Hongyu (Frontiers in Genetics, 2020)
Abstract Evidence from clinical and epidemiological studies indicates that asthma is associated with allergic diseases including hay fever, allergic rhinitis, and eczema. Genetic analysis demonstrated that asthma had a positive genetic correlation with allergic diseases. A mendelian randomization (MR) analysis using the rs16969968 single nucleotide variant as the instrumental variable indicated that smoking was associated with increased risk of asthma. However, in a different MR analysis, smoking was significantly associated with reduced hay fever and reduced allergic sensitization risk. These findings revealed inconsistencies in the association of smoking with asthma and allergic diseases. Hence, we conducted an updated MR analysis to investigate the causal association between lifetime smoking and asthma risk using 124 genetic variants as the instrumental variables. No significant pleiotropy was detected using the MR-Egger intercept test. We found that increased lifetime smoking was significantly associated with decreased asthma risk using the inverse variance weighted (IVW) method (OR=0.97, 95% CI 0.956–0.986, P=1.77E−04), the weighted median regression method (OR=0.976, 95% CI 0.96–0.994, P=8.00E−03), and the MR-Egger method (OR=0.919, 95% CI 0.847–0.998, P=4.5E−02). Importantly, MR-PRESSO MR analysis also indicated significant association between increased lifetime smoking and decreased asthma risk with OR=0.971, 95% CI 0.956–0.986, P=2.69E-04. After removing the outlier, MR-PRESSO outlier test further supported the significant association with OR=0.971, 95% CI 0.959–0.984, P=1.57E-05.